Les pouvoirs d’office du juge des procédures collectives de l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) et les principes cardinaux du procès - Biboum Bikay, François (Juridical Tribune - Review of Comparative and International Law, 2015)
The law of collective proceedings for clearing off depts which replaces the former bankruptcy law pursues an economic objective the reason why it carries certain exceptions to the common procedure law. As such, the judge of collective proceedings has powers of initiative in the institution and conduct of the trial. He can thus of his own initiative open the collective proceeding. The aim of this study is to confront the judge's office powers with the cardinal principles of the trial. The expected result should help verify the compatibility of those powers with the requirements of a fair trial. A hypothesis emerges that automatically powers that deviate somewhat to the cardinal principles of the trial, are justified by the aim of safeguarding collective interests pursued by the insolvency judge.